2010
DOI: 10.1002/jbm.a.32726
|View full text |Cite
|
Sign up to set email alerts
|

Polyester copolymer scaffolds enhance expression of bone markers in osteoblast‐like cells

Abstract: In tissue engineering, the resorbable aliphatic polyester poly(L-lactide) (PLLA) is used as scaffolds in bone regeneration. Copolymers of poly(L-lactide)-co-(epsilon-caprolactone) [poly(LLA-co-CL)] and poly(L-lactide)-co-(1,5-dioxepan-2-one) [poly(LLA-co-DXO)], with superior mechanical properties to PLLA, have been developed to be used as scaffolds, but the influence on the osteogenic potential is unclear. This in vitro study of test scaffolds of poly(LLA-co-CL) and poly(LLA-co-DXO) using PLLA scaffolds as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 38 publications
0
36
0
6
Order By: Relevance
“…The pattern of ECM production exhibited by the HOBs is similar to that observed by other groups using different types of scaffolds, including poly( l -lactide) (PLLA) copolymers, RADA-16, PEG and gelatin gels. 10,22,30,31 …”
Section: Resultsmentioning
confidence: 99%
“…The pattern of ECM production exhibited by the HOBs is similar to that observed by other groups using different types of scaffolds, including poly( l -lactide) (PLLA) copolymers, RADA-16, PEG and gelatin gels. 10,22,30,31 …”
Section: Resultsmentioning
confidence: 99%
“…Several authors have shown that various scaffolding materials, including polymer, can induce ectopic bone formation [8,11,12]. In vitro findings have also suggested that poly(LLA-co-DXO) scaffolds enhance differentiation of osteogenic cells [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Biocompatibility was confirmed according to ISO/EN 109935 guidelines [6] and a series of studies has demonstrated that cell lines with osteoprogenitor potential, such as rat-and human-derived bone marrow stromal cells (MSC), periodontal ligament cells and human osteoblast-like cells, attach, spread and proliferate well on these constructs [7][8][9][10]. Moreover, the scaffolds stimulate osteogenic differentiation of rat and human bone marrow stromal cells and human osteoblastlike cells [7,8,10]. A recent animal study, using a rat calvarial defect model, showed that implantation of scaffolds seeded with endothelial cells and MSC promoted rapid bone formation [11].…”
Section: Introductionmentioning
confidence: 99%